To review practice in the management of rhesus D-negative women during pregnancy. (16th November 2010) - Kadwadkar, N; Lo, J
Abstract : The Department of Health has recommended that 'Routine Antenatal Anti-D Prophylaxis' (RAADP) should be offered to all non-sensitised Rhesus D (RhD)-negative pregnant women at 28 and 34 weeks of gestation.1 The difference between RAADP and prophylactic anti-D given because of likely sensitisation event should be clearly explained.1 The Royal College of Gynaecologists has recommended the administration of additional antenatal prophylaxis following sensitisation events and postnatal prophylaxis to all non-sensitised RhD-negative women with RhD-positive babies.2 This retrospective study aimed to find out whether the management of Rhesus D-negative women during pregnancy was adhered to in accordance to the NICE and Green-top guidelines. Thirty-one cases of non-sensitised RhD-negative pregnant women selected randomly between January 2006 and September 2007. Our results showed that 93% of women had RAADP and 96% of women had additional antenatal anti-D prophylaxis following sensitisation events. Sixteen per cent of women who declined RAADP received postnatal prophylaxis without documentation of their consent. The reason[s] for their refusal to administer RAADP but accepted postnatal prophylaxis was not documented. Our study showed that majority of women received RAADP and additional antenatal anti-D prophylaxis. Whether women truly understood the actual implication of refusal of RAADP was unclear. Improvement in documentation regarding the reasons for declining antenatal prophylaxis might help the improvement in uptake of anti-D prophylaxis.